Cao Fei’s Imagery of the Chinese Female Cyborg as A Posthuman Identity In 21st Century China (Proceeding of the International Conference on Arts and Humanities, 2022)
This paper examines Cao Fei’s early twenty-first century works which proposes a cyborgian future where Chinese women can take agency of their own body and thoughts through a second skin, to create their personal alternate histories. The paper begins with an exploration of the Artificial Intelligence (AI) to cyborg phenomenon across pop culture, contemporary art and governance. Drawing references from the current AI technology wars between China and America, this paper investigates; (1) China’s motivations behind this ploy, how it affects the marginalized female gender; (2) and focuses on Chinese multimedia artist Cao Fei’s early twenty-first century works, which responds to the social and urban conditions in China hinting on a cyborg solution to take on contemporaneous China. The research aims to convey the hidden qualities that make up the Chinese female cyborg in Cao Fei’s selected works and discusses the capabilities of this empath heroine, by way of a cybernetic adornment, for women in China’s Social Credit System (shehui xinyong tixi –SCS) society. The paper further discusses the body, gender and posthuman politics of the Chinese female cyborg by critiquing the stereotypes it perpetuates and the mind-body to machine ratio that alters the embodied humanness. The discussion concludes with the Chinese female cyborg as “new materialism” that is able to articulate Freud’s “bodily ego” concept and contributes to Donna Haraway’s request for a different relationship for nature/culture that we are faced with. This paper recognizes the patriarchal authoritarian conundrum that will continue to hinder greater equality for women in China and is a call-to-action to consider the many ways art may inform new technologies that can work to benefit all people.
Keywords: Chinese feminism; cyborg feminism; posthuman identity; cybernetic adornment; fashion biomimicry